The Effect of Knee Tuck Jump and Jump-To-Box Plyometric Training on Female Students’ Leg Muscle Strength and Flexibility in Volleyball Extracurricular Activity - Rismayanthi, Cerika; Salam, Nur Alfitra; Alim, Abdul; Miftachurochmah, Yulvia (Physical Education Theory and Methodology, 2024)
Study purpose. This study aimed to investigate the effects of Knee Tuck Jump or Jump to Box plyometric training and to determine their effectiveness in increasing leg muscle strength and flexibility in female students participating in volleyball extracurriculars. Materials and methods. This study used a quasi-experimental design. Twenty-four female students were randomly selected as samples and then divided into two categories: 12 students receiving Knee Tuck Jump training (age: 17.08±0.51) and 12 students receiving Jump to Box training (age: 17.00±0.60). All participants performed the initial and final tests using the Vertical Jump and sit-and-reach tests. To analyze the data, the t-test was used to determine the differences in variables between the pretest and posttest in the experimental group. Results. In the Knee Tuck Jump group, a significant improvement in VJ (P=0.000) and sit-&-reach tests (P=0.000) was observed. In addition, Knee Tuck Jump was considered to be more effective in increasing the students’ flexibility, because the t value of sit-&-reach test (14.075) was higher than that of VJ (13.811). Similarly, the Jump to Box group also showed a significant improvement in VJ (P=0.000) and sit-&-reach (P=0.000) tests. However, Jump to Box was deemed to be more effective in increasing the students’ leg muscle strength, as the t value of VJ (26.086) was higher than that of sit-&-reach test (9.594). Conclusions. Based on the research findings, it can be concluded that plyometric exercises, specifically KTJ and JB, have a significant and positive impact on the lower limb muscle strength and flexibility in female students participating in volleyball extracurricular activities. Despite both demonstrating significant positive effects, KTJ training is more effective in improving flexibility compared to JB, while JB is more effective in enhancing lower limb muscle strength compared to KTJ.